The Effects Of Using Portfolio In Writing Activities Aimed At Developing The Arabic Language Discourse Competence Of 1st Secondary Grade Students In Housha Secondary School For Girls In Jordan - Mamdouh Alqadi, Haitham (European Scientific Journal, ESJ, 2016)
The focus of the present study is the investigation of the effects of using portfolio in writing activities aimed at developing the Arabic language discourse competence of 1st secondary grade students in Housha secondary school for girls in Jordan. The study sample was chosen purposefully. It consists of two sections for the first secondary grade, namely: the experimental group and the control group. The experimental group consisted of twenty (20) females, while the control group consisted of twenty (20) females as well. The treatment represented in using portfolio was conducted through an academic semester that lasted for three months. At the end of the semester, both groups were tested in using discourse competence components. The results showed that there was a statistically significant difference in favor of the experimental group in using elements of discourse competence due to the treatment. In light of the results, the researcher presented some recommendations at the end of the study.